The nexus between mortgage financing and economic growth in Malaysia: a comparative analysis of islamic and conventional banks - Afsheen, Saima (2022)
The study examines the impact of mortgage finance on Malaysia economic growth from the fourth quarter of 2006 to the fourth quarter of 2020. An important and distinct case is provided by dual banking system in Malaysia in order to interplay between macroeconomic variables (non-performing loan, house price index, inflation rate, lending rate, and world governance indicators) and mortgage finance provide by Islamic banks (IBS) and conventional banks (CBS). The study employs basic statistics, unit root test, a Johansen cointegration test and Vector Error Correction Model (VECM) for the empirical relationship. Finding of the study shows that, both in the short-run and long-run, there is positive and significant relationship mortgage finance and economic growth. Furthermore, Granger causality test is employed to examine the causal relationship between economic growth and the defined variables used in this study. It is worthy to note that the Granger causality test is not just used to determine the relationship between the independent and dependent variables, but also to ascertain the direction of the causality between them. Finally, for the assessment of parameter stability, the cumulative sum (CUSUM) and the CUSUM of squares (CUSUMSQ) tests are applied. This study conclude that efficient financial system can be led by the availability of mortgage finance. Therefore, in order to boost the development of mortgage finance the government should provide fruitful policies in the medium to long terms.